Pyrrhidivalva sordida - Rybalkin, Sergey A. (Zenodo, 2020)
Pyrrhidivalva sordida (Butler, 1881) Fig. 3: 18 Material. Russia: Kunashir Island, 4.5 km NW Mendeleyevo Airport, Tretyakovo village, 1.09– 10.09.2019, 7 ex., leg. S. Rybalkin. Distribution. Russia (Sakhalin, Khabarovsky Krai, Amur Region, Primorsky Krai), Japan (Hokkaido, Honshu, Shikoku, Kyushu), Korea, China, Taiwan (Lelej 2016). The species is recorded for the first time from the Kuril Islands. Spaelotis ravida (Denis & Schiffermuller, 1775) Fig. 3: 19 Material. Russia: Kunashir Island, 4.5 km NW Mendeleyevo Airport, Tretyakovo village, 4.09– 19.09.2019, 8 ex., leg. S. Rybalkin. Distribution. Russia (Kamchatka, Khabarovsky Krai, Sakhalin, Kuril Islands (Iturup Island), S. Siberia, W. Siberia, Ural, European Russia, N. Caucasus), Japan (Hokkaido), Korea, China, Mongolia, Kazakhstan, Middle Asia, Near East, Baltic countries, Belarus, Ukraine, Europe, N. India, Pakistan (Lelej 2016). The species is recorded for the first time from Kunashir Island. Published as part of Rybalkin, Sergey A., 2020, On the knowledge of Lepidoptera of Kunashir Island, Russia, pp. 98-105 in Amurian Zoological Journal XII (2) on pages 101-104, DOI:10.33910/2686-9519-2020-12-2-98-105, http://zenodo.org/record/11362013